Oskar Ursinus papers - Ursinus, Oskar
Correspondence, notes, manuscript articles by Ursinus and others, clippings, printed matter, charts, maps, sketches, blueprints, photographs, and other papers relating to the development of German aeronautics during the first half of the 20th century. Subjects include military aviation in World War I, the German aircraft industry, altitude flying, engines, instruments, aircraft, rockets, aeronautical societies, and aeronautical sports events.
Aviator, engineer, and journalist.
Collection material in English and German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Confiscated by the U.S. Army in Europe in World War II. Transferred to the Library of Congress Aeronautics Division from Wright-Patterson Air Force Base (Ohio) in 1948.
Keywords: Aeronautical instruments; Aeronautical sports; Aeronautics; Aeronautics -- Societies, etc; Aeronautics -- Germany; Airplanes; Airplanes -- Motors; Airships; Flight; Rocketry -- Germany; World War, 1914-1918 -- Aerial operations; Aviators; Engineers; Journalists